Bronius Pranskus-Žalionis - critic, scientist, professor - Liudvika Lisenkaitė (Literatūra (Vilnius))
The article is devoted to one of the first Lithuanian Marxist literary researchers, a well-known critic and historian of literature, Professor B. Pranskus-Žalionis. The author of the article shows in detail the years of studies of B. Pranskus at the Moscow State University (1923-1926) and at the Institute of Linguistic and Literary Research (1926-1929), emphasizes his educational and scientific contacts with V. Friche, investigates the formation of his literary-aesthetic views and the confirmation of these views in his practical activity.